2002
DOI: 10.1002/jms.370
|View full text |Cite
|
Sign up to set email alerts
|

A capsule review of recent studies on the application of mass spectrometry in the analysis of Chinese medicinal herbs

Abstract: Chinese herbal medicine is gaining increasing popularity worldwide as an alternative approach to the development of pharmaceuticals in therapeutic applications. Chemical characterization and compositional analysis of Chinese medicines provide the necessary scientific basis for the discovery and development of new drugs of natural origin. Applications of mass spectrometry in the analysis of Chinese herbal medicines have been growing rapidly in recent years owing to the rapid technical advances and increasing av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
82
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(85 citation statements)
references
References 88 publications
1
82
0
Order By: Relevance
“…The optimized parameters in the negative ion mode were as follows: ion spray voltage, 4.5 kV; sheath gas (N 2 ), 45 arbitrary units; auxiliary gas (N 2 ), 10 units; capillary temperature, 320°C; capillary voltage, Ϫ15 V. For full scan MS analysis, the spectra were recorded in the range of m/z 120 -800. A data-dependent program was used in the liquid chromatography-tandem mass spectrometry analysis so that the two most abundant ions in each scan were selected and subjected to MS/MS and MS 3 analyses. The collision-induced dissociation (CID) energy was adjusted to 45%.…”
Section: Mass Spectrometrymentioning
confidence: 99%
See 1 more Smart Citation
“…The optimized parameters in the negative ion mode were as follows: ion spray voltage, 4.5 kV; sheath gas (N 2 ), 45 arbitrary units; auxiliary gas (N 2 ), 10 units; capillary temperature, 320°C; capillary voltage, Ϫ15 V. For full scan MS analysis, the spectra were recorded in the range of m/z 120 -800. A data-dependent program was used in the liquid chromatography-tandem mass spectrometry analysis so that the two most abundant ions in each scan were selected and subjected to MS/MS and MS 3 analyses. The collision-induced dissociation (CID) energy was adjusted to 45%.…”
Section: Mass Spectrometrymentioning
confidence: 99%
“…The plant extract, however, is a very complex mixture, and contains a variety of secondary metabolites. A potent and currently widely used technique to analyze plant extracts is fingerprinting, especially by high-performance liquid chromatography-diode array detection (HPLC-DAD) [3]. An informative and convincing fingerprint should have most of the diagnostic peaks elucidated.…”
mentioning
confidence: 99%
“…Liquid chromatography coupled with mass spectrometry (LC/MS) is a powerful technique for the analysis of complex botanical extracts [15,16]. HPLC is efficient in separating chemical compounds in a mixture, and MS provides abundant information for structural elucidation of the compounds when tandem mass spectrometry (MS n ) is applied.…”
mentioning
confidence: 99%
“…More recently, electrospray ionization (ESI) has become one of the most effective analytical tools for the structural characterization of a variety of polar and thermally labile molecules, e.g., polypeptides, carbohydrates and natural glycosides [19 -22]. Recent studies have reported the use of ESI-MS for determination of saponins with higher sensitivity and better reproducibility than the other types of ionization [23][24][25][26][27][28]. Moreover multistage mass spectrometry has great advantages for characterization of compounds by providing structural information [24,25,[27][28][29][30][31].…”
mentioning
confidence: 99%